When Fuzzy was afraid of losing his mother - Maier, Inger M.; Candon, Jennifer (Washington, D.C. Magination Press, 2005)
Fuzzy the sheep does not want his mother to leave his side, but she finds a way to help him feel more secure about her absence.
At head of title: Fuzzy the little sheep.
"Ages 3-7".--Cover p. [4].
Keywords: Separation anxiety -- Fiction; Mother and child -- Fiction; Sheep -- Fiction